Study of Energy-Friendly and Energy-Saving Concepts in the Residental Design of IAI Malang - Redi Sigit Febrianto; Bambang Joko Wiji Utomo (ESE International Journal (Environmental Science and Engineering), 2020)
Contemporary architect designed houses tend to be environmentally friendly and energy efficient. An architect-designed residence is not only a place of refuge, a reflection of character, lifestyle and shows existence, but also must be energy efficient and environmentally friendly. This study seeks to describe what are the elements of environmentally friendly architecture and energy efficient architecture in the residential design of IAI Malang. The research design uses a mix method, namely exploring (qualitative) as well as trying to explain (quantitative). The research strategy is hermeneutics. The data collection method is secondary data. Using 3 analytical methods, namely descriptive analysis, thematic analysis and comparative analysis. The output of the research is a diagram of the elements forming sustainable architecture in 10 residential samples by architect IAI Malang.